2006
DOI: 10.1189/jlb.0706468
|View full text |Cite
|
Sign up to set email alerts
|

Increasing numbers of hepatic dendritic cells promote HMGB1-mediated ischemia-reperfusion injury

Abstract: Endogenous ligands released from damaged cells, so-called damage-associated molecular pattern molecules (DAMPs), activate innate signaling pathways including the TLRs. We have shown that hepatic, warm ischemia and reperfusion (I/R) injury, generating local, noninfectious DAMPs, promotes inflammation, which is largely TLR4-dependent. Here, we demonstrate that increasing dendritic cell (DC) numbers enhance inflammation and organ injury after hepatic I/R. High-mobility group box 1 (HMGB1), a NF released by necrot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
2
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(81 citation statements)
references
References 58 publications
0
75
2
1
Order By: Relevance
“…Recent studies have suggested that the initial damage to cells along with the activation of inflammatory signaling are involved the release of endogenous damage-associated molecular pattern (DAMP) signaling molecules from damaged/ischemic cells or IRI tissues. High mobility group box 1 (HMGB 1), a known DAMP molecule, can trigger cell-mediated inflammatory responses by enhancing the expression of TLR4 and increasing reactivity to it and other DAMP molecules 5 . HMGB1 was considered to be a novel key molecule during the IRI after KTx 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that the initial damage to cells along with the activation of inflammatory signaling are involved the release of endogenous damage-associated molecular pattern (DAMP) signaling molecules from damaged/ischemic cells or IRI tissues. High mobility group box 1 (HMGB 1), a known DAMP molecule, can trigger cell-mediated inflammatory responses by enhancing the expression of TLR4 and increasing reactivity to it and other DAMP molecules 5 . HMGB1 was considered to be a novel key molecule during the IRI after KTx 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Original magnification was ϫ50. other studies have demonstrated that dendritic cells are activated by Toll-like receptor-mediated pathway and increase their expression of MHC class II during hepatic I/R injury, leading to antigen-dependent activation of CD4 ϩ T cells (30,40). Moreover, blockade of TCR signaling with cyclosporine treatment is known to reduce hepatic I/R injury (24,35).…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial cells also express costimulatory molecules and can serve as APCs for T cell activation [86]. The important role of DCs in mediating immune responses in hepatic IRI was also reported in part by enhanced TLR4 reactivity [87]. TLRs are expressed abundantly on DCs and play a pivotal role in DC activation [68], which suggests a potential involvement of DC in the immune responses in IRI.…”
Section: Dendritic Cells and B Cells In Irimentioning
confidence: 99%